2022
DOI: 10.1186/s13023-022-02490-8
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance literacy and health services access barriers in Niemann–Pick disease: the patient and caregiver voice

Abstract: Background Major challenges to health care access include low health insurance literacy, prohibitive costs, and insurance barriers. Niemann–Pick disease (NPD), comprising acid sphingomyelinase deficiency (ASMD) and Niemann–Pick type C (NPC), is a group of rare, autosomal recessive, highly heterogeneous, neurovisceral, life-threatening, relentlessly progressive lysosomal disorders. Patients experience debilitating systemic and neurological symptoms and substantial emotional and financial stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Age, ethnicity, and preferred language were all found to be significant demographic factors, and insurance and SSN status were found to be significant socioeconomic factors. These results corroborate findings from other clinical trial enrollment studies [ 13 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Age, ethnicity, and preferred language were all found to be significant demographic factors, and insurance and SSN status were found to be significant socioeconomic factors. These results corroborate findings from other clinical trial enrollment studies [ 13 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…While studies on insurance and SSN status in relation to clinical trial participation are scarce, published studies have reported that patients with fewer financial resources, such as medical insurance, are often underrepresented in cancer clinical trials [ 34 ]. Uninsured individuals have also been reported to be more likely to struggle with accessing necessary medical care while simultaneously experiencing higher rates of disease onset and severity [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%